2022
DOI: 10.3389/fpsyg.2022.935773
|View full text |Cite
|
Sign up to set email alerts
|

Team diversity, conflict, and trust: Evidence from the health sector

Abstract: The current study aims to determine the impact of diversity and intra-team trust on conflict within the health sector of Pakistan. This study also measures the moderating role of trust in the relationship between diversity and conflict among team members. Data was collected using personally administered questionnaires from 61 teams, including 377 respondents working in 4 public sector hospitals in Pakistan, which were selected using a simple random sampling technique. The results revealed that diversity (as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Gender was not a significant predictor, which contradicts previous studies that have suggested that gender heterogeneity in a group is negatively correlated with students’ interactions among early adolescents [ 42 , 43 ]. Numerous studies have examined the effect of demographic diversity, such as age or gender, on group performance with inconsistent results [ 64 – 66 ]. This inconsistency may be related to the context dependence of demographic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Gender was not a significant predictor, which contradicts previous studies that have suggested that gender heterogeneity in a group is negatively correlated with students’ interactions among early adolescents [ 42 , 43 ]. Numerous studies have examined the effect of demographic diversity, such as age or gender, on group performance with inconsistent results [ 64 – 66 ]. This inconsistency may be related to the context dependence of demographic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the theoretical results, we found that culturally diverse teams, both in-person or virtual, have a number of advantages including increased innovation (Jones et al, 2020) and creativity (Tang, 2019), enhanced decision-making (Stahl & Maznevski, 2021), building of high level of competence and cultural awareness among team members (Burkiewicz & Knap-Stefaniuk, 2022;Shepherd et al, 2019;Stahl & Maznevski, 2021), improved adaptability and flexibility, readiness to work in changing work environment (Burkiewicz & Knap-Stefaniuk, 2022), understanding of global market development and the implementation of best practices for global business (Kipnis et al, 2019). At the same time, the findings show that multinational teams may lead to communication challenges (Mwamba & Malik, 2022), mismatched expectations caused by information gaps (Burkiewicz & Knap-Stefaniuk, 2022;Shrivastava & Pandey, 2022), difficulties in team building, and lack of synergy among team members (Gabelica & Popov, 2020), emergence of conflicts, limited social interaction and insufficient mutual support, trust issues (Nawaz et al, 2022), and delays in decision-making (Stahl & Maznevski, 2021). Figure 1 summarizes the advantages and disadvantages of multinational teams.…”
Section: Monocultural Working Environment Multicultural Working Envir...mentioning
confidence: 99%
“…Taking this into consideration, we found that there are 11 project management approaches in global business development that are applied in the context of cultural diversity and are oriented towards maximize cultural differences within the team. They are the following: cultural awareness assessment (Jones et al, 2020;Shepherd et al, 2019;Tian, 2020), customized communication (Baptista, 2022;Cizmaș et al, 2020;Mwamba & Malik, 2022), cultural liaison (Cripe & Burleigh, 2022;Tian, 2020), adaptive leadership styles (Anwer et al, 2022;Burkiewicz & Knap-Stefaniuk, 2022), inclusive decision-making (Stahl & Maznevski, 2021), cross-cultural training (Baptista, 2022;Jones et al, 2020;Tian, 2020), team building (Gabelica & Popov, 2020), use of feedback (Baptista, 2022;Ponomareva et al, 2022), conflict resolution (Mwamba & Malik, 2022;Nawaz et al, 2022), recognizing cultural differences (Anwer et al, 2022;Tian, 2020), implementation of diverse projects (Baptista, 2022;Tian, 2020). Table 2 analyzes the project management approaches for global business development in the context of cultural diversity.…”
Section: Disadvantagesmentioning
confidence: 99%
“…Family motivation is an under-researched concept and one of the potential sources of inspiration and motivation for working people in a different context (Menges et al, 2017;Tariq and Ding, 2018;Erum et al, 2020). There are individuals whose jobs are toxic, low paying, boring, without an opportunity for advancement, and without monetary benefits or bonuses, but still, they are types of jobs (Nawaz et al, 2022). Motivation is either extrinsic or intrinsic (Gagné and Deci, 2005), but if both motivational forces are absent, why do people still perform their jobs?…”
Section: Self-determination Theorymentioning
confidence: 99%